Gotong Royong Menuju Kompetisi Pasar: Amandemen UUD 1945 Tahun 2002 dan Ketimpangan Keadilan dalam Ekonomi Digital di Indonesia - Al Syahrin, M Najeri (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
The shift in economic power structures following the amendments to the 1945 Constitution, particularly through Article 33 paragraph (4), marked a turning point in Indonesia's economic paradigm, moving from a mutual cooperation orientation toward market competition. The purpose of this study is to analyze this context in the expansion of the digital economy and its implications for the principle of equitable efficiency as mandated by Article 33 paragraph (4). Using the justice approach of Caporaso and Levine (1992) and the constitutional framework of Article 33 paragraph (4), this study describes how the efficiency and competition orientations underlying digital economic development tend to conflict with the values of social justice that are at the core of the Pancasila people's economy. Digital markets operating based on commercial logic result in an unequal distribution of access and profits, strengthen the dominance of large actors, and weaken the state's role in creating equality. Empirical impacts are evident in the inequality of digital infrastructure and access, the dominance of digital start-ups with high foreign capital expansion costs, e-commerce concentration, consumer data security and protection, technology adoption and capabilities across business scales, access to financing for MSMEs, and the lack of social security protection for informal workers. Without strong state policy intervention to expand digital infrastructure and ensure the inclusive distribution of economic benefits, the digital economy has the potential to deepen socio-economic inequality in Indonesia.